2011
DOI: 10.1002/stem.644
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Quiescent and Active States of Endogenous Adult Neural Stem Cells: Identification and Characterization

Abstract: The adult mammalian central nervous system (CNS) lacks the capacity for regeneration, making it a highly sought-after topic for researchers. The identification of neural stem cells (NSCs) in the adult CNS wiped out a long-held dogma that the adult brain contains a set number of neurons and is incapable of replacing them. The discovery of adult NSCs (aNSCs) stoked the fire for researchers who dream of brain self-repair. Unfortunately, the quiescent nature and limited plasticity of aNSCs diminish their regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 57 publications
1
89
0
1
Order By: Relevance
“…To examine these cells in more detail, RT-qPCR analysis was performed on a number of genes involved in oxidative stress, hypoxia and apoptosis. Notably, the potent antioxidant glutathione peroxidase 1 24 , the cell cycle exit regulator p21 25 , the transcription factor and regulator of cell survival on oxidative stress, Foxo1 26 , hypoxia-inducible factor 3a2 27 , a transcription factor that regulates the adaptive responses to hypoxia, and angiopoietin 1, which promotes muscle stem cell quiescence 28 , were all upregulated in expression in post mortem muscle stem cells. In addition, the tumour suppressor p53, which upregulates p21, and is involved in a variety of stress responses 29 , was significantly upregulated in post mortem muscle stem cells, as was Ptx3 30 , which is part of the inflammatory response and has a role at the late phase of apoptosis.…”
Section: Viability Of Human and Mouse Muscle Stem Cells Post Mortemmentioning
confidence: 99%
“…To examine these cells in more detail, RT-qPCR analysis was performed on a number of genes involved in oxidative stress, hypoxia and apoptosis. Notably, the potent antioxidant glutathione peroxidase 1 24 , the cell cycle exit regulator p21 25 , the transcription factor and regulator of cell survival on oxidative stress, Foxo1 26 , hypoxia-inducible factor 3a2 27 , a transcription factor that regulates the adaptive responses to hypoxia, and angiopoietin 1, which promotes muscle stem cell quiescence 28 , were all upregulated in expression in post mortem muscle stem cells. In addition, the tumour suppressor p53, which upregulates p21, and is involved in a variety of stress responses 29 , was significantly upregulated in post mortem muscle stem cells, as was Ptx3 30 , which is part of the inflammatory response and has a role at the late phase of apoptosis.…”
Section: Viability Of Human and Mouse Muscle Stem Cells Post Mortemmentioning
confidence: 99%
“…The ability to switch between active and quiescent states is a fundamental feature of adult stem cells, including the neurogenic astrocytes of the SVZ and DG (Cheung and Rando, 2013;Wang et al, 2011). These cells operate within neurogenic niches that are set during embryonic development and are thought to play an active role in regulating their quiescence and their capacity to produce neurons (Fuentealba et al, 2012;Kriegstein and Alvarez-Buylla, 2009).…”
Section: ) Although Parenchymal Astrocytesmentioning
confidence: 99%
“…Moreover, although BMSCs have been shown to be able to differentiate into several mesenchymal tissues, including tendons, 12 the possibility of isolating tendon-specific stem cells is desirable, as progenitor cells are more prone to differentiate into those cell types that belong to the tissue in which they reside 32 : they form stem cell reservoirs, the ''niches'' 10 that can regulate the physiological turnover of differentiated cells, also in organs such as the brain and the heart, which have been recently proven to undergo some regeneration during aging. 5,33 Along this line, a very recent study reported an in-depth comparison of the phenotype and the regenerative potential of rat TDSCs and BMSCs. 31 Interestingly, the authors found that TDSCs possess a higher proliferative rate and multilineage differentiation potential than BMSCs, therefore concluding that TDSCs are a very promising stem cell source for musculoskeletal tissue engineering.…”
mentioning
confidence: 97%